2012
DOI: 10.1242/jeb.073023
|View full text |Cite
|
Sign up to set email alerts
|

Low O2 acclimation shifts the hypoxia avoidance behaviour of snapper (Pagrus auratus) with only subtle changes in aerobic and anaerobic function

Abstract: SUMMARYIt was hypothesised that chronic hypoxia acclimation (preconditioning) would alter the behavioural low-O 2 avoidance strategy of fish as a result of both aerobic and anaerobic physiological adaptations. Avoidance and physiological responses of juvenile snapper (Pagrus auratus) were therefore investigated following a 6week period of moderate hypoxia exposure (10.2-12.1kPa P O2 , 21±1°C) and compared with those of normoxic controls (P O2 =20-21kPa, 21±1°C). The critical oxygen pressure (P crit ) limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 46 publications
7
43
3
Order By: Relevance
“…Yet another possibility is that severe hypoxia may be perceived by fish as a noxious or painful stimulus. Some authors have identified an aversive behaviour that may lead fish away from regions of severe hypoxia and toward the surface (Petersen and Petersen, 1990;Weltzien et al, 1999;Poulsen et al, 2011;Cook et al, 2013). In the present study, ASR behaviour in zebrafish was punctuated with brief trips to the bottom of the chamber before returning rapidly to the surface.…”
Section: Asr As a Chemoreflexsupporting
confidence: 48%
“…Yet another possibility is that severe hypoxia may be perceived by fish as a noxious or painful stimulus. Some authors have identified an aversive behaviour that may lead fish away from regions of severe hypoxia and toward the surface (Petersen and Petersen, 1990;Weltzien et al, 1999;Poulsen et al, 2011;Cook et al, 2013). In the present study, ASR behaviour in zebrafish was punctuated with brief trips to the bottom of the chamber before returning rapidly to the surface.…”
Section: Asr As a Chemoreflexsupporting
confidence: 48%
“…One explanation for this discrepancy is that a developmentally appropriate P 50 value may be guarded in early life stages regardless of environmental O 2 levels to ensure adequate unloading at the tissues, as seen in some adult teleosts (e.g. Cook et al, 2013). Although hypoxic larvae are developmentally delayed and smaller than their normoxic counterparts, they still experience an eightfold increase in mass between Stages 27 and 35, and their mass is only 7 and 29% less than stage-matched normoxic Stage 33 and 35 larvae, respectively.…”
Section: Early Ontogenetic Strategies For Coping With Hypoxiamentioning
confidence: 99%
“…Interestingly, a recent study by Urschel and O'Brien (2009) Leak respiration rates observed when both complexes I and II were activated at temperatures below ABT only constitute about 10% of state III rates obtained at the same temperature (Figure 2). This value is small compared to about 50% of state III with only complex I activated in snapper mitochondria (Cook et al 2013), and slightly lower than 15% of state III found in permeabilized heart ventricle fibers of triplefin blennies at 15°C (Hilton et al 2010). However, similar values have been obtained for the notothenioid L. nudifrons (10.2% at 0°C), which suggest a low proton leakiness of the inner mitochondrial membrane in notothenioids (Hardewig et al 1999b).…”
Section: Thermal Tolerance In Pleuragramma Antarcticummentioning
confidence: 68%
“…More recent studies utilized titrations including PM to activate complex I, PMS to activate both complexes I and II and others have used rotenone as a complex I inhibitor in the presence of S to activate solely complex II (Weinstein and Somero 1998;Hardewig et al 1999a;Lannig et al 2005). The addition of glutamate and the overall combination of PMGS in a single run has been utilized in snappers recently (Cook et al 2013), and our study constitutes the first attempt in notothenioids. Recent studies on human muscle mitochondria showed additive effects of those substrates, mainly due to the convergent nature of the ETS (Gnaiger 2009).…”
Section: Antarctic Teleostsmentioning
confidence: 99%
See 1 more Smart Citation